Perfil epidemiológico de la embarazada adolescente adscrita en unidad de medicina familiar No 80 - Zamudio Raya, César Augusto (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Pregnancy in adolescents has a high prevalence in México. This involves serious complications in the mother, product, family and society. In UMF No. 80 the epidemiological profile of adolescent pregnant women is unknown. OBJECTIVE: To describe the epidemiological profile of pregnant adolescents enrolled in UMF No. 80. MATERIAL AND METHODS: Observational, descriptive, retrospective, cross-sectional study. In adolescents with pregnancy from November 2015 to July 2016, enrolled in UMF 80, patients with psychiatric illnesses were excluded and the surveys were not concluded at 100%. A sociodemographic, gynecological-obstetrical, FF-SIL for family functionality, Graffar for socio-economic stratum and a questionnaire on interfamily violence of the National Institute of Women of México were applied. RESULTS: In a sample of 72 patients, 98.6% were found in late adolescence, 1.4% in the early stages, without drug addiction 80.6%, smoking 11.1%, alcohol 6.9%, drugs 1.4%, socioeconomic level 72.22% worker, 19.94% low, 4.17% 4.17% marginal, IVU with cervicovaginitis 44.44%, 25% IVU, 11.11% cervicovaginitis, 2.78% with EHE, 16.67% without pathology, family function 45.83% moderate dysfunction, 37.50% functional, 15.28% dysfunctional, 1.39% severely dysfunctional, interfamily violence 83.33% abusive relationship, 8.33% first abuse, 6.94% severe abuse, 1.39% dangerous abuse. CONCLUSIONS: Pregnant patients enrolled in UMF No. 80 are over the age of 15 years, above 80% without drug addiction, socioeconomic status predominant worker, high percentage of patients with IVU and cervicovaginitis independent or associated, most with some degree of family dysfunction, in its entirety with interfamily violence.

El embarazo en adolescentes tiene alta prevalencia en México. Esto implica serias complicaciones en la madre, producto, familia y sociedad. En UMF No. 80 se desconoce el perfil epidemiológico de las embarazadas adolescentes adscritas. OBJETIVO: Describir perfil epidemiológico de la adolescente embarazada adscrita a UMF No. 80. MATERIAL Y MÉTODOS: Estudio observacional, descriptivo, retrospectivo, transversal. En adolescentes con embarazo en periodo de noviembre 2015 a julio 2016 adscritas a UMF 80, se excluyeron pacientes con enfermedades psiquiátricas y que no concluyeron al 100% las encuestas. Se aplicó encuesta de antecedentes sociodemográficos, gineco-obstétricos, FF-SIL para funcionalidad familiar, Graffar para estrato socio-económico y cuestionario de violencia intrafamiliar del Instituto Nacional de Mujeres de México. RESULTADO: En muestra de 72 pacientes se encontró 98.6% en adolescencia tardía, 1.4% temprana, sin toxicomanías 80.6%, tabaquismo 11.1%, alcohol 6.9%, drogas 1.4%, nivel socioeconómico 72.22% obrero, 19.94% bajo, 4.17% medio y 4.17% marginal, IVU con cervicovaginitis 44.44%, 25% IVU, 11.11% cervicovaginitis, 2.78% con EHE, 16.67% sin patología, funcionalidad familiar 45.83% moderada disfuncionalidad, 37.50% funcional, 15.28% disfuncional, 1.39% severamente disfuncional, violencia intrafamiliar 83.33% relación abusiva, 8.33% primer nivel de abuso, 6.94% abuso severo, 1.39% abuso peligroso. CONCLUSIONES: Las pacientes embarazadas adscritas en la UMF No. 80 más de 95% son mayores de 15 años, arriba del 80% sin toxicomanías, nivel socioeconómico predominante obrero, gran porcentaje cursan con IVU y cervicovaginitis independientes o asociadas, la mayoría con algún grado de disfunción familiar, en su totalidad con violencia intrafamiliar.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4303; info:eu-repo/classification/cti/3; FCMB-E-2018-0280; Perfil epidemiológico; Unidad de medicina familiar; Funcionallidad